The Influence of Academic Success of Islamic Religious Education and Social Media Involvement on Student Morality - Al Mursyidi, Busro Muhammad; Darmawan, Didit (Al-Fikru: Jurnal Ilmiah, 2023)
Education is an effort to convey knowledge through guidance, direction, and training throughout individual life from inside and outside educational institutions, with the aim of preparing students to contribute to future life, which also includes the development of knowledge, moral values, and ethics so that higher education levels not only reflect intellectual intelligence, but also the ability to form good morals through the right learning process. This study aims to analyse the effect of Islamic Religious Education learning achievement and the use of social media on the moral formation of MTs Miftahiyah Yasi Bangkalan students. The research used is quantitative, with data collection through questionnaires and observations of 75 students. The results of the regression analysis show that Islamic Religious Education learning achievement and the use of social media significantly affect the morals of students. This finding contributes to the understanding of the relationship between Islamic religious education and social media to shape the moral formation of students in the digital era.